Comparison between microwave and traditional water bath cooking on saltiness perception, water distribution and microstructure of grass crap meat. (November 2019) - Wang, Xuejiao; Muhoza, Bertrand; Wang, Xingwei; Feng, Tingting; Xia, Shuqin; Zhang, Xiaoming
Abstract: The aim of this study was to investigate the effect of microwave and traditional water bath on physical and chemical properties of grass carp meat and the impact on saltiness perception. The surface hydrophobicity and Fourier transform infrared spectroscopy (FTIR) results showed that microwave made meat proteins unfold less than water bath. The low degree of protein unfolding of meat cooked by microwave caused the changes in water distribution and the formation of a compact microstructure, which were related to the enhancement of saltiness perception. Furthermore, the meat cooked by microwave had lower cooking loss and shear force compared to traditional water bath. The sodium level remained and the distribution of Na and Cl in meat matrix further demonstrated sensory analysis result that the grass carp meat cooked by microwave was saltier than that cooked by water bath. The current research also provided a new approach to reduce salt consumption in fish cooking for home cooking or food industry. Graphical abstract: Unlabelled Image Highlights: Microwave cooking could improve saltiness perception of grass carp meat. Salt retention in meat was related to water distribution and microstructure. Water distribution differences was due to changes of protein tertiary structure. Microstructure differences was caused by changes of protein tertiary structure.